Psychosocial Difficulties in Preschool-Age Children with Beckwith-Wiedemann Syndrome: An Exploratory Study - Niccolò Butti; Annalisa Castagna; Rosario Montirosso (MDPI AG, 2022)
Beckwith-Wiedemann syndrome (BWS) is a rare overgrowth disease and is not usually associated with intellectual delay. Living with a chronic illness condition such as BWS, however, might affect emotional-behavioral functioning and psychosocial development. To investigate this issue, parents of 30 children with BWS between 1.5 and 6 years old compiled standardized questionnaires assessing the presence of emotional-behavioral and developmental problems. The group mean scores in each scale of behavioral problems fell within the average range. Nevertheless, 23% of the sample presented scores beyond the risk threshold for social withdrawal. As regards psychomotor development, a lower mean score was reliable in the social domain compared to other developmental scales, and in the gross-motor compared to fine-motor functions. Moreover, scores in the at-risk band were reliable in almost half of the children for social development. Notably, older age was overall associated with higher emotional-behavioral and developmental difficulties, while no other socio-demographic or clinical variables accounted for the scores obtained in the questionnaires. These findings ask for a wider consideration by health and educational professionals of the psychosocial functioning of children with BWS, so as to early detect at-risk conditions and eventually promote adequate interventions.